Risk factors for sporadic Shiga toxin-producing Escherichia coli infections in children, Argentina - Rivas, Marta (2008)
Fil: Rivas, Marta. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.